Gandhian Social work and his Constructive Programme: Contextualizing his Satayagrah for the peaceful world. - Mrinal, Madhur; Kumar, Upmesh (SPC Journal of Social Sciences, 2020)
Paper highlights three Satyagragh of Gandhiji. Champaran Satyagragh peasant movement was first Satyagragh prevailing situation of indigo planters and role of Gandhiji. It also enumerates his philosophy for world peace through global programme of nonviolence and truthfulness, constructive programs and his concept of the social work education. It concludes Gandhian principles can transform Global world for peace through Professional social work education by incorporating the Constructive Program as suggested by Gandhi. His philosophy- sataygragh, ahimsa and swadeshi are well included in Constructive Programmes for making more relevant for peace today. The social work practitioner may feel teaching and training of Social work student should be based on Constructive Programme for making Sarvodaya Society and a Sarvodaya social Order as Gandhi enshrined in his philosophy.Â Â